2021
DOI: 10.1016/j.jsurg.2020.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Medical Student Assessment in the Time of COVID-19

Abstract: Background Medical student education in the era of the COVID-19 outbreak is vastly different than the standard education we have become accustomed to. Medical student assessment is an important aspect of adjusting curriculums in the era of increased virtual learning. Methods Students took our previously validated free response clinical skills exam (CSE) at the end of the scheduled clerkship as an open-book exam to eliminate any concern for breaches in the honor code and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 2 publications
1
48
0
2
Order By: Relevance
“…The impact of interruption of clinical clerkship in internal medicine due to the COVID-19 pandemic and whether the experience of clinical clerkship during the pandemic has affected performance in theory and clinical exams of our students is not known. However, in Columbia, 17 students who sat their exams during the pandemic had higher scores compared with historic cohort. However, these high scores were attributed to the open book nature of the exams and that students had more time to prepare for them.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The impact of interruption of clinical clerkship in internal medicine due to the COVID-19 pandemic and whether the experience of clinical clerkship during the pandemic has affected performance in theory and clinical exams of our students is not known. However, in Columbia, 17 students who sat their exams during the pandemic had higher scores compared with historic cohort. However, these high scores were attributed to the open book nature of the exams and that students had more time to prepare for them.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have evaluated the impact of the COVID-19 pandemic on surgical training 13 and fellowships, 14 radiology residency, 15 gastroenterology residency 16 and assessment of medical students. 17 Between 40% and 100% of surgical residents reported severe impact of the COVID-19 pandemic on their training. 13 However, there is no published study examining experience of medical students or residence in general internal medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Ensuring safety during tests has been an area of concern, with medical schools evaluating and implementing the use of virtually proctored shelf examinations. 78 At the time of writing this review, there were no plans for delivering videoproctored examinations from the American Board of Internal Medicine; however, precautions are in place to mitigate transmission per the Centers for Disease Control and Prevention and World Health Organization guidelines, including use of masks during the administered board examinations. 79 The American Board of Internal Medicine has also provided alternative testing dates for various examinations and an option to defer the examination to the following year.…”
Section: Challenges With Interviewingmentioning
confidence: 99%
“…Besides interrupting with clinical clerkships, the COVID-19 pandemic has brought a myriad of challenges in clinical bedside teaching since medical students now have limited direct patient care activities, such as physical examinations and procedures [11,12]. In this study, we found that nearly Previous studies have evaluated the impact of the COVID-19 pandemic on surgical training [13] and fellowships [14], radiology residency [15], gastroenterology residency [16] and assessment of medical students [17].…”
Section: Discussionmentioning
confidence: 74%
“…Previous studies have evaluated the impact of the COVID-19 pandemic on surgical training [13] and fellowships [14], radiology residency [15], gastroenterology residency [16] and assessment of medical students [17]. Between 40 and 100% of surgical residents reported severe impact of the COVID-19 pandemic on their training [13].…”
Section: Discussionmentioning
confidence: 99%